1999
DOI: 10.1039/a705676a
|View full text |Cite
|
Sign up to set email alerts
|

Natural sesquiterpenoids

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 259 publications
(277 reference statements)
0
9
0
Order By: Relevance
“…Plant species belonging to the family Asteraceae are known for their content of sesquiterpenes which have been reported to serve as toxic or feeding deterrents to insect herbivores . In the present studies, two sesquiterpene lactones, alantolactone and isoalantolactone isolated from I. racemosa , exerted a growth‐inhibiting effect on S. litura .…”
Section: Discussionmentioning
confidence: 99%
“…Plant species belonging to the family Asteraceae are known for their content of sesquiterpenes which have been reported to serve as toxic or feeding deterrents to insect herbivores . In the present studies, two sesquiterpene lactones, alantolactone and isoalantolactone isolated from I. racemosa , exerted a growth‐inhibiting effect on S. litura .…”
Section: Discussionmentioning
confidence: 99%
“…Basidiomycetes have an inherent ability to produce terpenoids, which is the largest and most diverse class of natural products (Quin et al ., ; Schmidt‐Dannert, ). A wide variety of sesquiterpenoids with an extensive repertoire of backbone structures have been isolated and characterized (Stadler et al ., ; Shiono et al ., ; Kim et al ., ; Li et al ., ; Yoshikawa et al ., ; Kramer and Abraham, ; Fraga, ). A rich history of biochemical studies on sesquiterpene metabolism has established a general scheme that structural diversity of sesquiterpenoids is accomplished by concomitant actions of both sesquiterpene synthases (STSs) and terpene‐modifying enzymes, such as cytochrome P450 monooxygenases (P450s) (Christianson, ; Quin et al ., ; Weitzel and Simonsen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Kayser and Kolodziej () reported that position of alcoholic group affect the fungicidal activity of compound. Hence it can be concluded hydroxyl groups was perquisite for toxicity and position of hydroxyl group was most important as the enzyme‐alcohol complex formed in stereo‐specific manner and compounds with hydroxyl groups showed high solubility in water causing more toxicity (Fraga, ). Daucone showed fungicidal activity due to the presence of ketone group.…”
Section: Resultsmentioning
confidence: 99%